(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Due to enlarged worldwide competition and the assortment of family structures and morals, work-life balance (WLB) is a decisive issue for working professionals in today’s fastpaced society. People find it difficult to maintain a healthy balance among their individual and professional lives. Their proficiency and job satisfaction are being impacted by a number of mental and emotional troubles that are being caused by these inequalities. Organisations need a deeper understanding of how conflicts between work and family duties impact their operating environment. According to professionals life balance (WLB) is the scope to which a person is equally involved in their professional position and family responsibility. Perfect time management avoids conflicts between work and personal commitments.